Adaptation of Madagascar Students Living in Indonesia to the Problems of Stereotypes in Intercultural Communication - Narimalaromisa Tiana James; Rahma Surya Dewi; Sarmiati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Since the introduction of the Darmasiswa and KNB programmes and the opening of enrolment for Malagasy students in Indonesia, they have faced significant challenges in cross-cultural adaptation. This study examines stereotypes related to the origins and physical appearance of Malagasy students based on Edmund Husserl's phenomenology through a qualitative descriptive approach involving in-depth interviews, observations, and documentary studies of nine informants. The findings reveal three dimensions: stereotypical experiences (physical assessment, social labelling, impact on self-confidence); cultural intermediation strategies (acting as ‘ambassadors’, coping mechanisms, support from the Malagasy community); and the management of communication misunderstandings through linguistic adjustments and reduced speech in situations prone to prejudice. Keywords: Adaptation, Communication, Intercultural, Problem, Stereotype, Students from Madagascar